Creating Interracial Intimacies: British North America, Canada, and the Transatlantic World, 1830–1914 - Morgan, Cecilia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractThis article explores the domestic relationships of a number of interracial couples: Kahkewaquonaby/Peter Jones and Eliza Field; Nahnebahwequa/ Catherine Sutton and William Sutton; Kahgegagahbowh/George Copway and Elizabeth Howell; and John Ojijatekah Brant-Sero, Mary McGrath, and Frances Kirby. These unions took place within the context of and, in a number of instances, because of Native peoples’ movements across a multiple boundaries and borders within British North America, Canada, and Britain. Based in both Canadian Native historiography and work in colonial and imperial history, particularly that which focuses on gender, this article argues that international networks, such as nineteenth-century evangelicalism, the missionary movement, and circuits of performance, shaped such unions and played a central, constitutive role in bringing these individuals together. However, the article also points to the importance of exploring such large-scale processes at the biographic and individual level. It points to the different outcomes and dynamics of these relationships and argues that no one category or mode of scholarly explanation can account for these couples’ fates. The article also points to multiple and varied combinations of gender, class, and race in these relationships. It thus offers another dimension to the historiography on Native-white intimate relationships in North America which, to date, has focused mostly on relationships between white men and Native or mixed-race/Métis women. The article concludes by considering how these relationships complicate our understanding of commonly used concepts in imperial history, specifically those of domesticity and home.